The Effect of Growth Hormone on the Clinical Outcomes of Poor Ovarian Reserve Patients Undergoing in vitro Fertilization/Intracytoplasmic Sperm Injection Treatment: A Retrospective Study Based on POSEIDON Criteria - Cai, Mei-hong; Gao, Lin-zhi; Liang, Xiao-yan; Fang, Cong; Wu, Yao-qiu; Yang, Xing (Frontiers in Endocrinology, 2019)
The aim of this retrospective analysis is to explore whether growth hormone (GH) pretreatment is beneficial for patients with poor ovarian reserve undertaking in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) treatment. Poor ovarian reserve patients with anti-Mullerian hormone (AMH) <1.2 ng/mL were recruited and divided into the GH adjuvant group (GH+ group) and the counterpart without GH pretreatment (GH- group). One-to-one case-control matching was performed to adjust essential confounding factors between the GH+ group and GH- group. A total of 676 cycles were included in the present study with 338 cycles in each group. Conventional ovarian stimulation protocols were applied for ART treatment. Patients were further divided into POSEIDON group 3 (PG3, age <35 years) and POSEIDON group 4 (PG4, age ≥35 years), based on POSEIDON criteria. The demographic data, cycle characteristics and clinical outcomes between the GH+ group and GH- group, as well as in the further stratified analysis of PG3 and PG4 were compared. GH adjuvant showed a beneficial effect on the ovarian response and live birth rate in poor ovarian reserve patients. Further stratification revealed that in PG4, there was a significantly increased number of good-quality embryos in the GH+ group compared to the GH- group (1.58±1.71 vs. 1.25±1.55, P =0.032), accompanied by a reduced miscarriage rate and a greatly improved live birth rate (29.89% vs. 17.65%, P =0.028). GH adjuvant failed to promote the live birth rate in PG3. In conclusion, GH pretreatment is advantageous by elevating ovarian response and correlated with an improved live birth rate and reduced miscarriage rate in POSEIDON poor ovarian reserve patients older than 35.